Peran Guru Sosiologi sebagai Motivator dalam Mengoptimalkan Kedisiplinan Siswa Kelas 10 MA Darul Huda Wonodadi Blitar - Galuh Ajeng Mutiara Putri Muis; Yudi krisno Wicaksono (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
Student discipline problems such as tardiness, lack of learning readiness, and low compliance with school rules are still common in secondary education. This study examines the role of sociology teachers as motivators in optimizing the discipline of 10th-grade students at MA Darul Huda Wonodadi Blitar, focusing on three aspects: 1. The role of teachers as motivators, 2. Challenges faced, 3. The impact on student discipline. A qualitative approach with a case study type was used, involving in-depth interviews, observations, and documentation with the principal, sociology teachers, guidance counselors, and students. Data analysis used Miles, Huberman, and Saldana, with triangulation and member checks to test the validity of the data. The findings show that sociology teachers apply motivational strategies through 1. Personal approach, 2. Communicative, 3. Advice, 4. Role model, 5. Positive reinforcement. This strategy successfully shifts the orientation of student compliance from fear of punishment to awareness of internal responsibility. The challenges faced include low student learning motivation, 1. Internal student factors, 2. Smartphone misuse, 3. Social environment. The impact of the role of motivators is seen in 1. Transformation of compliance, 2. Increased activity, 3. Improvement of ethics and manners. This study provides a theoretical contribution by showing that intrinsic and extrinsic motivation strategies, not just rule enforcement, can shape sustainable student discipline.